The traditional portion of a Vietnamese colonial port city : commerce, politics, and the origin of Hải Phòng (1802-1888) - Vu, Duong Luan (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article examines commercial activities, the impact of political interaction between the local powers and foreign colonialists, and other issues in the making of colonial port cities in Asia. By analyzing the formation history of Hải Phòng, one of largest seaports in Vietnam during the nineteenth century, the author of this study argues that indigenous factors played a more important role than other factors of the standard Western requirements for European powers to select places to establish ports in the early colonial period. Therefore, the convenience of an early modern trading center and the inland-connecting ability of Hải Phòng made it quickly become used as the main naval base in early expeditions of the French in Tonkin. Consequently, despite the difficulties of water transport to and from a seaport influenced by rivers and tides, the disagreement of scientist and the lack of infrastructure, the government of Indochina eventually decided to select Hải Phòng as the location to build the major port of northern Vietnam in the late nineteenth century. It is also the reason for this city not only maintaining marine exchange and transport under the domination of French colonialism but also remaining as an irreplaceable port in the northern part of modern Vietnam during the long twentieth century.